METHODOLOGICAL TOOLS FOR THE DEVELOPMENT OF SOCIAL SERVICES MARKET IN RURAL SETTLEMENTS (Revista Inclusiones, 2020)
The scientific problem solved in the framework of this article is to identify effective tools to stimulate competition in the rural social services market. The theoretical justification of tools to stimulate competition in the social services market is carried out as part of a study of causal relationships with factors that determine the behavior of entrepreneurs. The first logical construct, reflecting the provisions of the theory of the company, involves an explanation of the result of stimulation by the market structure that has developed under the influence of fundamental factors. The second logical approach, reflecting the reaction of entrepreneurs to incentive measures, is based on the theory of performance and notes the presence of weak reactions to changes in the market structure and a stronger reaction when declaring improved performance due to special institutional and infrastructural conditions for the functioning of the business.